Ankle joint contact loads and displacement in syndesmosis injuries repaired with Tightropes compared to screw fixation in a static model. Issue 11 (November 2019) - Pang, Eric Quan; Bedigrew, Katherine; Palanca, Ariel; Behn, Anthony W; Hunt, Kenneth J; Chou, Loretta
Highlights: Near anatomic restoration of tibiotalar pressure mechanics is achieved with two TightRopes or two 3.5 mm screws with axial load alone applied. With low levels of ER, the TightRope group more closely matched the native contact and pressure mechanics than the screw group. These findings may effect implant selection, postoperative weightbearing protocols, and reduction of post-traumatic arthritis. Abstract: Background: The effect of syndesmotic fixation on restoration of pressure mechanics in the setting of a syndesmotic injury is largely unknown. The purpose of this study is to examine the contact mechanics of the tibiotalar joint following syndesmosis fixation with screws versus a flexible fixation device for complete syndesmotic injury. Methods: Six matched pairs of cadaveric below knee specimens were dissected and motion capture trackers were fixed to the tibia, fibula, and talus and a pressure sensor was placed in the tibiotalar joint. Each specimen was first tested intact with axial compressive load followed by external rotation while maintaining axial compression. Next, syndesmotic ligaments were sectioned and randomly assigned to repair with either two TightRopes® or two 3.5 mm cortical screws and the protocol was repeated. Mean contact pressure, peak pressure, reduction in contact area, translation of the center of pressure, and relative talar and fibular motion were calculated. Specimens were then cyclically loaded in external rotation and surviving specimens were loaded in external rotation to failure. Results: No differences in pressure measurements were observed between the intact and instrumented states during axial load. Mean contact presure relative to intact testing was increased in the screw group at 5 Nm and 7.5 Nm torque. Likewise, peak pressure was increased in the TightRope group at 7.5 Nm torque. There was no change in center of pressure in the TightRope group at any threshold; however, at every threshold tested there was significant medial and anterior translation in the screw group relative to the intact state. Conclusion: Either screws or TightRope fixation is adequate with AL alone. With lower amounts of torque, the TightRope group appears to have contact and pressure mechanics that more closely match native mechanics.